J Pengaruh Sumber Daya Manusia dalam Bidang Ekonomi di Desa Ulumambi Kecamatan Bambang Kabupaten Mamasa: Pengaruh Sumber Daya Manusia dalam Bidang Ekonomi di Desa Ulumambi Kecamatan Bambang Kabupaten Mamasa - Andi Firdaniah (STIM LASHARAN JAYA MAKASSAR, 2022)
This study aims to determine wheter the Ulumambi people are able to manage and develop human resources,especially in the economi field. This research approach is qualitative research. The subjects of this study were all people in the village of Ulumambi, Bambang sub-district,Mamasa district. The results showed that the management and development of human resources in the village of Ulumambi greatly influenced the community. Based on the results obtained, it can be concluded that the influence of human resources is very important for the community to face changes that are more advanced. Keywords: Human resources, economics.